CERN’s Balancing Act Between Unity and Disunity: The ‘‘Sister Experiments’’ UA1 and UA2 and CERN’s First Nobel Prize - Panoutsopoulos, G.; Arabatzis, T. (Physics in Perspective, 2021)
In this paper, we employ Ian Hacking’s insight that ‘‘unity’’ has a double meaning, singleness and harmonious integration, to revisit a major episode from the recent history of CERN: the UA1 and UA2 experiments in the early 1980s, which led to the discovery of the W and Z bosons. CERN is a complex institution, where diverse groups are called upon to cooperate. We argue that this lack of unity, in the first sense of the term, is counterbalanced by specific mechanisms of integration, so that CERN achieves its standing as a unified organization. The UA1/UA2 episode highlights this interplay between unity and disunity. The UA2 experiment was designed and carried out in order to confirm the validity of the results obtained by UA1. The two experimental teams, working independently and with different mentalities, built separate detectors and refrained from systematically sharing their data. This gave rise to strong antagonisms and diametrically opposed opinions over what conclusions could legitimately be drawn from the resulting data. Our analysis focuses on the mechanisms which compensated for that disunity and eventually led to a unified consensus between UA1 and UA2.